Acute Budd Chiari Syndrome - Uddin, AFMH; Wareshuzzaman, M; Banik, RK; Saha, SK; Nath, NC; Shil, BC; Faruque, MO; Dhar, SC (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Budd-Chiari syndrome (BCS) is a rare disease in population characterized by hepatic venous outflow obstruction at a site that may vary from the level of the small hepatic veins up to the junction of the inferior vena cava with the right atrium . Here we presented a case of 35 year old male who presented with abdominal pain, abdominal distension and leg oedema . Subsequent physical examination, laboratory data, abdominal ultrasonography and duplex study all confirmed the diagnosis of BCS with Protein C , protein S , and antithrombin III deficiency . But we were unable to detect whether these factor deficiency were primary or secondary. Genetic study may be used to elucidate the cause. Whether primary or secondary, standard protocol should be used to treat Budd Chiari syndrome with these factor deficiency. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21009 J Bangladesh Coll Phys Surg 2013; 31: 223-226